2018
DOI: 10.3390/urbansci2010024
|View full text |Cite
|
Sign up to set email alerts
|

Retailing of Processed Dairy and Grain Products in Mali: Evidence from a City Retail Outlet Inventory

Abstract: Abstract:As in many sub-Saharan African countries, Mali is experiencing an unprecedented rate of urbanization and, with it, changes to its agri-food system. As more people live in urban areas, the demand for processed foods has been increasing rapidly. These changes have important implications for food and nutrition security. Yet, little is known about the scale and scope of the retailing of processed foods. To better understand this segment, we conducted a city retail outlet inventory of processed dairy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
4
11
1
Order By: Relevance
“…This study adds to the emerging picture of the transformation of the urban food system across Africa. Our findings confirm the prevalence of imported food products in West Africa, as shown by similar inventories conducted recently (Liverpool Tasie et al, 2016; Theriault et al, 2018). However, unlike the Mali case, where Theriault et al (2018) found no international supermarket chains and only a few local supermarkets in the capital Bamako, we see penetration of international and local chain supermarkets across all cities in Ghana.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This study adds to the emerging picture of the transformation of the urban food system across Africa. Our findings confirm the prevalence of imported food products in West Africa, as shown by similar inventories conducted recently (Liverpool Tasie et al, 2016; Theriault et al, 2018). However, unlike the Mali case, where Theriault et al (2018) found no international supermarket chains and only a few local supermarkets in the capital Bamako, we see penetration of international and local chain supermarkets across all cities in Ghana.…”
Section: Resultssupporting
confidence: 92%
“…Our findings confirm the prevalence of imported food products in West Africa, as shown by similar inventories conducted recently (Liverpool Tasie et al, 2016; Theriault et al, 2018). However, unlike the Mali case, where Theriault et al (2018) found no international supermarket chains and only a few local supermarkets in the capital Bamako, we see penetration of international and local chain supermarkets across all cities in Ghana. Although inventories in Tanzania showed locally manufactured grain products dominating imports (Ijumba et al, 2015), the opposite holds true in Ghana (this study), Mali (Theriault et al, 2018) and Nigeria (Liverpool Tasie et al, 2016).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Each commune encapsulates several neighborhoods. Five types of outlets that represented the variety of commercial structures in the capital city were targeted [45]:…”
Section: Rapid Market Assessmentmentioning
confidence: 99%